Reliability and validity of a computer-based assessment of cognitive and non-cognitive facets of problem-solving competence in the business domain - Rausch, Andreas [Verfasser]; Seifried, Jürgen [Verfasser]; Wuttke, Eveline [Verfasser]; Kögler, Kristina [Verfasser]; Brandt, Steffen [Verfasser] (My University, 2016)
"To measure higher-order outcomes of vocational education and training (VET) we developed a computer-based assessment of domain-specific problem-solving competence. In modeling problem-solving competence, we distinguish four components of competence: (1) knowledge application, (2) metacognition, (3) self-concept, and (4) interest as well as thirteen facets of competence, each of which is assigned to one of the four components. With regard to ecological and content validity, rather than apply highly structured items (e.g. multiple choice items), we developed three authentic problem scenarios and provided an open-ended problem space in terms of an authentic office simulation. The assessment was aimed at apprentice industrial clerks at the end of a 3-year apprenticeship program and focused on the domain of controlling (i.e., support of managerial decisions, cost planning, cost control, cost accounting, etc.). In order to assess the non-cognitive components in our competence model, we implemented an integrated measurement of self-concept and interest that we refer to as 'Embedded Experience Sampling' (EES). The empirical section is based on a study with 780 VET students from three commercial training occupations in Germany (industrial clerks and apprentices from two similar VET programs). The focus of the contribution is on testing a theoretically derived competence model based on item response theory, the implemented scoring methods and reliability of the instrument." (Authors' abstract, BIBB-Doku)
Keywords: L 3 Lehr-Lern-Forschung; L 6.3.1 Diagnose- & Messinstrumente; L 2.3.2 Handlungs- & problemorientierte Methoden; S 6.4.1 Kaufleute; Lehr-Lern-Forschung; Kompetenzfeststellung; Kompetenzdiagnostik; Kompetenzmodell; Problemlösen; Kaufmännische Ausbildung; Empirische Untersuchung